Fabrication of graphene-oxide and zeolite loaded polyvinylidene fluoride reverse osmosis membrane for saltwater remediation. (November 2022) - Hassan, Faiza; Mushtaq, Rabia; Saghar, Sadia; Younas, Umer; Pervaiz, Muhammad; Aljuwayid, Ahmed muteb; Habila, Mohamed A.; Sillanpaa, Mika
Abstract: Incorporation of inorganic and organic materials in polymer has contributed well towards the development of advanced reverse-osmosis membranes; with greater permeation, and salt rejection potential. We are reporting, Zeolite/GO/PVDF based thin-film composite membranes that were successfully synthesized by solution casting process, an eco-friendly, low-cost, and biocompatible technique. PVDF membranes modified with different ratios of GO/Zeo (0.03, 0.05 and 0.07) were characterized by FTIR, SEM, XRD, TGA, and DSC. Membranes were then tested for its potential for water permeation and salt rejection abilities. As prepared membranes owe better pore-distribution, a moderate degree of crystallinity and high absorption capability that is highly needed for micro-filtration phenomena used for desalination of saline water. The modified membranes exhibited enhanced water permeability up to 28.9 L/m 2 h as compared to pure PVDF membrane having water permeability flux of 15.6 L/m 2 h. Salt-rejection ability was found increasing for the membranes (up to 98%) modified with different concentration of GO/Zeo, as compare to pure PVDF membrane (82%). During water permeation and salt rejection studies, no deleterious impact was noted for modified PVDF membranes. This development will entail an efficient approach to furnish high-level performance reverse-osmosis membranes, with greater osmotic-pressure bearing capacity and higher stability. Graphical abstract: Image 1 Highlights: Polyvinylidene fluoride membranes with enhanced properties have been prepared. Properties have been enhanced by adding GO and Zeolite nanofillers. Membranes have been characterized using FTIR, SEM, XRD and TGA techniques. The membranes exhibited excellent desalination potential.